Мир эмоций в нашей жизни - Кудин, Вячеслав Александрович (НТУ "ХПИ", 2012)
In the article the problem of emotions is analysed in the vital functions of man.Found out intercommunication between the emotional sphere of osobistoti and perception of the world. Except for it,certain clear vzaemoobumovlennist' between perceptible,emotional in life of man and by progress in all spheres of activity.
Keywords: эмоции; чувства; страх; гнев